How Greek Students Perceive Concepts Related to Geoenvironment: A Semiotics Content Analysis - Georgousis, Efthymios; Savelidi, Maria; Savelides, Socrates; Mosios, Spyros; Holokolos, Maximos-Vasileios; Hara Drinia (Geosciences, 2022)
In order to design a geoeducation program in the context of the possibilities given to the Experimental Schools of Greece of Lower Secondary Education, teachers identified the need for diagnostically assess students’ understanding of basic concepts of the geoenvironment and particularly the concepts of geodiversity, geoheritage, geoethics and geotourism. In addition, there was a need to apply the educational technique of creating cognitive conflicts in order to promote the scientific perceptions of these concepts. Thus, research questions were identified which led the research to assess the current latent state of students’ perceptions regarding the thematic areas of the concepts and to identify concepts whose perceptions can be used in the educational process in order to achieve effective cognitive conflicts in order to promote scientific perceptions of them. The students briefly answered a four-question questionnaire, wherein each question examined their perceptions regarding the four concepts of geoenvironment: geodiversity, geoheritage, geoethics and geotourism. All 45 students of the geoeducation program that took part in the survey were aged between 12 and 15 years old. The qualitative research strategy approach was selected and specifically the hybrid technique of semiotics content analysis in combination with thematic analysis. This technique was selected due to the need to identify, code, categorize and count both obvious and latent meanings in the students’ written answers; these meanings were related to the four concepts under examination. The results of the research show that the current latent state of students’ perceptions regarding the thematic fields of the four concepts of the geoenvironment can be considered as particularly confused since the majority of students did not understand the concepts as they are employed in the international literature. The research also highlighted concepts that can be used by teachers in their efforts to develop students’ clear or even scientifically acceptable perceptions for the concepts of geodiversity, geoheritage, geoethics and geotourism in the thematic field of the geoenvironment.